Influence of Smoking Cigarettes on Cerebral Blood Flow Parameters. (January 2015) - Kochanowicz, Jan; Lewko, Jolanta; Rutkowski, Robert; Turek, Grzegorz; Sieskiewicz, Andrzej; Lyson, Tomasz; Mariak, Zenon
Introduction: While chronic cigarette smoking can lead to increased risk of stroke, the acute effects of smoking have not been established. We studied the changes in blood flow parameters in the major cerebral arteries caused by smoking one cigarette. Method: Using transcranial color-coded sonography (TCCS), we studied the anterior cerebral artery (ACA), middle cerebral artery (MCA), posterior cerebral artery (PCA), and the internal carotid artery (ICA) of 36 healthy male volunteers before and after they smoked one cigarette. Results: Blood flow velocity increased to a different degree in all but one of the arteries examined after participants smoked a single cigarette: The end diastolic velocity increased significantly by 7.8% in the PCA, 8% in the ACA, and 14.4% in the MCA. The peak systolic velocity increased significantly by 7.5% in the MCA. Blood flow velocity remained unchanged in the ICA only. Blood pressure and heart rate increased as did the flow velocity ratio for the MCA/ICA. The pulsatility index decreased after smoking from 0.92 ± 0.13 to 0.87 ± 0.14 in the MCA, 0.93 ± 0.15 to 0.87 ± 0.13 in the ACA, and 0.95 ± 0.17 to 0.89 ± 0.16 in the PCA. Conclusions: The results suggest that the direct effect of smoking on cerebral circulation includes peripheral vasodilatation with possible constriction of the main trunk of the basal cerebral arteries.